Bacteriological profile of aerobic and anaerobic isolates of trophic ulcer in leprosy: A study from Eastern India - Revanta Saha; Somenath Sarkar; Monalisa Majumder; Gautam Banerjee (Wolters Kluwer Medknow Publications, 2019)
Introduction: Trophic ulcer is a dreaded complication of leprosy. Secondary infection compounds the damage to the already neglected ulcer. Aims: To find out the bacterial pathogens in the isolates from trophic ulcers of leprosy and to find the drug sensitivity of the aerobic isolates so as to start a suitable antibiotic therapy. Methodology: An institution-based, cross-sectional study done over a period of 2 years. Swab was taken from the deeper part of the ulcer. It was put on a suitable culture media. Bacteriological profile was determined and antibiogram was done subsequently. Results: Sixty patients with trophic ulcer secondary to leprosy were screened, among which all were screened for aerobic isolates and 38 were screened for anaerobic isolates. Among the aerobic isolates, 88% of patients were culture-positive. The most common organism was Staphylococcus aureus(37.7%), followed by Pseudomonas aeruginosa (22.64%), Proteus mirabilis (15.09%), Escherischia coli (13.2%), Klebsiella (9.43%). Maximum overall sensitivity was seen with amikacin (93.1%) and linezolid (89.65%). Maximum overall resistance was noted with cotrimoxazole (58.62%) and coamoxiclav (51.72%). Among the 38 patients cultured for anaerobic isolates, 17 were culture-positive for anaerobic organisms. Isolates showing Peptococcus were 6 (15.7%), purely Peptostreptococcus were 4 (10.5%), purely bacteroides were 3 (7.8%), and mixed growths were 4 (10.5%). Conclusion: Secondary bacterial infection is quite common in leprosy trophic ulcers. The most common organism was Staphylococcus aureus. Isolates were mostly sensitive to amikacin and linezolid and resistant to cotrimoxazole and coamoxiclav. Anaerobic isolates were not uncommon, with Peptococcus being the most common among them.